Harvest age data for catla families produced in 2024 - Hamilton, Matthew (2025)
As part of the WorldFish Carp Genetic Improvement Program, the fish size data (depth, standard length, width, total weight) for catla were collected at harvest from 27th October 2025 to 27th November 2025